Relations Low Birth Weight (LBW) With Height Body For Toddlers Age 36-48 Months In The Kauman Tulungagung Health Center In 2019 - Farida, Farida; Shintiya Dewi Subektiningsih (Journal of Global Research in Public Health, 2019)
Low Birth Weight (LBW) is the weight of babies born less than 2500 grams, this can affect growth, especially in subsequent toddler height. Abnormal height growth in infants is not only influenced by low birth weight factors but there are still many other factors that affect, but it is thought to have something to do with low birth weight. The purpose of this study was to determine the relationship between Low Birth Weight (LBW) with Height body for Toddlers Age 36-48 months in the KaumanTulungagung Health Center in 2019. The design of this study was observational analyticby method retrospective. The study was conducted on June 14th-21st, 2019. The population was all infants born to LBW aged 36-48 months in the Kauman Health Center Work Area using a total sampling technique with a total of 32 respondents. Retrieval of data using questionnaires and measurements of height. Dataanalyzedwith the test of correlation statisticalspearman rho. The results were obtained from 29 respondents (100%) with Low Birth Weight (LBW), most respondents had normal height, as many as 19 respondents (65.5%), while from 3 respondents (100%) with Very Low Birth Weight (LBWR) ) there are almost half of the respondents have a normal height that is as much as 1 respondent (33.3%). The results of the correlation test Spearman rho obtained values ​​ρ = 0.204 and α = 0.05 which means the value (ρ ≥ 0.05) so that Ho is accepted meaning that there is no LBW relationship with the height of toddlers aged 36-48 months.It was concluded that body weight at birth did not have a significant impact on the height of toddlers aged 36-48 months, this is because mothers are able to provide balanced nutrition to help their children grow. For this reason, it is necessary to educate mothers about balanced nutrition for toddlers, so that babies born with Low Birth Weight (LBW) can grow normally as they age.